Strategi Komunikasi Pemasaran Destinasi Wisata Park & Farm Sipirok Melalui Media Digital Instagram Dalam Meningkatkan Minat Pengunjung - Amriul Hakim Rangkuti; Leylia Khairani (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
The development of business in the field of tourism objects is currently very rapid, giving rise to competition to reach tourists between one tourist attraction and another. Rapid changes in the business environment have forced tourist attractions to continue to be active and creative in developing existing tourist sites and continuously making updates regarding strategies in marketing them. This study aims to determine "Marketing Communication Strategy for Sipirok Park And Farm Tourism Destinations through Instagram Digital Media in Increasing Visitor Interest". The method used in this research is descriptive qualitative. Data obtained from observations, interviews, and documentation using descriptive analysis techniques, namely describing the events studied. In this study, there were 5 resource persons, namely the manager of tourist attractions, employees of tourist attractions, and tourists. The research location is in Pasorminan Village, Sipirok District, South Tapanuli Regency. The results of this study are tourism managers in implementing marketing communication strategies in attracting tourists including three activities, including promotion activities through social media such as Instagram, and word of mouth. The second activity is a Place in the form of a comfortable, beautiful, and natural place. The third activity is Price in the form of very affordable entrance ticket prices.